„To nie jest poezja w całym słowa tego znaczeniu”. Pieśni żałobne getta Izabeli Gelbard - Karolak, Sylwia (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The main purpose of this article is to analyse the reception of Izabela Glebard’s (Czajka-Stachowicz’s) works, with particular emphasis on her only book of poety Pieśni żałobne getta . At first Gelbard intentionally chooses poetry, but after the experience of World War II, she leaves it completely and repleces by prose. The root cause of this state of affairs is the war trauma. Very important is also the critical attitude of the writer to her poems. These works have not been appreciated by literary critics who treat them as a document and testimony rather than a valuable poetry. It seems that the Gelbard poems, like all her works, are waiting for a new, contextual reading.